Quantum units from the topological engineering of molecular graphenoids - Lombardi, Federico; Lodi, Alessandro; Ma, Ji; Liu, Junzhi; Slota, Michael; Narita, Akimitsu; Myers, William K.; Muellen, Klaus; Feng, Xinliang; Bogani, Lapo (Science, 2019)
Robustly coherent spin centers that can be integrated into devices are a key ingredient of quantum technologies. Vacancies in semiconductors are excellent candidates, and theory predicts that defects in conjugated carbon materials should also display long coherence times. However, the quantum performance of carbon nanostructures has remained stunted by an inability to alter the sp2-carbon lattice with atomic precision. Here, we demonstrate that topological tailoring leads to superior quantum performance in molecular graphene nanostructures. We unravel the decoherence mechanisms, quantify nuclear and environmental effects, and observe spin-coherence times that outclass most nanomaterials. These results validate long-standing assumptions on the coherent behavior of topological defects in graphene and open up the possibility of introducing controlled quantum-coherent centers in the upcoming generation of carbon-based optoelectronic, electronic, and bioactive systems.
CRIS-Team Scopus Importer:2023-03-20